Woman Abuse in Canada: Sociological Reflections on the Past, Suggestions for the Future. (February 2014) - DeKeseredy, Walter S.; Dragiewicz, Molly
Woman abuse in Canada started receiving much sociological attention in the mid-1980s. This article describes past scholarly achievements, assesses current contributions, and suggests progressive ways of responding to future challenges. Special attention is given to how broader political economic forces help shape and constrain research on a variety of highly injurious male-to-female assaults that occur in private settings.